THE GLOBAL WORKFORCE: CHALLENGES AND OPPORTUNITIES IN INTERNATIONAL HUMAN RESOURCE MANAGEMENT - Waruwu, Eliyunus (Journal of Management Small and Medium Enterprises (SMEs), 2024)
This article investigates the challenges and opportunities in international human resource management (HRM) in Indonesia and its strategies. This qualitative study describes how companies manage HRM across various dimensions and addresses cultural differences, employment policies, and international recruitment factors. Data were obtained from secondary sources such as journals, books, and relevant industry reports. Challenges include cultural aspects, distance management, and international talent selection, while opportunities include enhancing competitive advantages and employee productivity. Strategies to address these challenges involve cross-cultural understanding, training, global communication technology, and policies accommodating differences in regulations between countries. Collaboration with international HR consultants is also recommended. With a holistic approach, international HRM can build an efficient and diverse global workforce, ensuring the success of global operations. Keywords: Global Workforce; International Human Resource Management; Challenge; Opportunities